Dose and image quality in computed tomography: an overview of Portuguese data - Coutinho, Ana Margarida (2017)
Computed Tomography exams expose patients to higher dose levels than most exams in radiology and the number of CT exams is increasing year after year in Portugal. In 2009 were performed 1.1 million CT exams and later in 2014, there were 1.6 million. This study aims to analyze dose and image quality data gathered from 180 distinct computed tomography systems, which represents 350 quality assurance interventions done in Portuguese national health units (mainland and islands) between 2014 and 2017. In the quality assurance interventions, a Catphan® 500 phantom was aligned in the center of the gantry and irradiated, for analysis of six parameters: CT numbers, slice thickness, low and high contrast resolution, uniformity and noise. Afterwards, an ionization chamber (Raysafe Xi CT sensor) was placed in the interior of a PMMA (polymethylmethacrylate) phantom and the Computed Tomography Dose Index (CTDI) was measured. Data analysis was performed using IBM SPSS v.22.0. In order to verify the CT numbers, four materials with different densities were analyzed and the mean CT numbers obtained were: -980 HU (Air), -943 HU (Teflon), -115 HU (Acrylic) and -99 HU (LDPE). The high contrast resolution values were determined for X-ray energies in a range of 80 kV to 100 kV at 200 mA and the mean spatial resolution obtained was 8 lp/cm with a gap size of 0,063 cm. When increasing the voltage to 130-140 kV the mean spatial resolution was 9 lp/cm with a gap size of 0,056 cm. Dose measured in the head and body scan techniques, with a voltage between 80 kV and 100 kV at 100 mA and 10 mm slice thickness was 6 my and 3 mGy, respectively. When increasing the voltage to 130-140 kV the mean values obtained were 23 mGy (head) and 12 mGy (body). These results show that with lower voltage the CTDI is four times lower while keeping an adequate spatial resolution. Adequate CT protocols are very important to ensure safety to all patients, and specifically designed pediatric protocols should be used, once children are more sensitive to the effects of ionizing radiation. It is important to adopt CT exams in order to minimize exposure while providing good diagnostic quality. In this study a comparison between adults and children protocols is made (using international publications like the ones form AAPM - American Association of Physicists in Medicine), using dose and resolution data from the Portuguese equipment.